2019
DOI: 10.1111/jvim.15425
|View full text |Cite
|
Sign up to set email alerts
|

Coding sequences of sarcoplasmic reticulum calcium ATPase regulatory peptides and expression of calcium regulatory genes in recurrent exertional rhabdomyolysis

Abstract: Background Sarcolipin (SLN), myoregulin (MRLN), and dwarf open reading frame (DWORF) are transmembrane regulators of the sarcoplasmic reticulum calcium transporting ATPase (SERCA) that we hypothesized played a role in recurrent exertional rhabdomyolysis (RER). Objectives Compare coding sequences of SLN, MRLN, DWORF across species and between RER and control horses. Compare expression of muscle Ca2+ regulatory genes between RER and control horses. Animals Twenty Thoroughbreds (TB), 5 Standardbreds (STD), 6 Quar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(49 citation statements)
references
References 53 publications
4
45
0
Order By: Relevance
“…RNA-seq data further indicated that PLN gene expression was undetected in rabbit muscle (SRA SAMN00013649 2 ). Thus, RNA-seq from horse and rabbit muscles provides results consistent with previous qRT-PCR studies which report that in non-rodent mammals such as rabbit, pig, and horse, SLN is the predominantly regulatory gene expressed in fast-twitch muscle (26,40). On the other hand, MRLN is the primary regulatory peptide gene expressed in mouse muscles (21).…”
Section: Transcription Of Sln Pln Mrln and Dworf Genes (Encoding Ssupporting
confidence: 87%
See 4 more Smart Citations
“…RNA-seq data further indicated that PLN gene expression was undetected in rabbit muscle (SRA SAMN00013649 2 ). Thus, RNA-seq from horse and rabbit muscles provides results consistent with previous qRT-PCR studies which report that in non-rodent mammals such as rabbit, pig, and horse, SLN is the predominantly regulatory gene expressed in fast-twitch muscle (26,40). On the other hand, MRLN is the primary regulatory peptide gene expressed in mouse muscles (21).…”
Section: Transcription Of Sln Pln Mrln and Dworf Genes (Encoding Ssupporting
confidence: 87%
“…We previously used quantitative reverse-transcriptase polymerase chain reaction (qRT-PCR) to quantify transcription of four genes (SLN, PLN, MRLN, and DWORF) encoding SERCA regulatory peptides in horse gluteus muscle, finding that SLN is the predominant regulatory peptide gene expressed in the middle gluteal muscle of Thoroughbred horses (40). Here we mined RNA-seq data (64) to quantify transcription of the same four genes encoding SERCA regulatory peptides (SLN, PLN, MRLN, and DWORF) in the middle gluteal muscle of six Arabian horses.…”
Section: Transcription Of Sln Pln Mrln and Dworf Genes (Encoding Smentioning
confidence: 99%
See 3 more Smart Citations